RIGHT TO SERVICE ACT IN KERALA AND ADMINISTRATIVE CULTURE: A CRITICAL PERSPECTIVE - Soumya S.; Madhusudhan B. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Right to Service (RTS) Act, enacted in Kerala in 2012, marks a crucial advancement towards improving the efficiency, transparency, and accountability in the delivery of public services. This legislation requires the government to offer public services within specific timeframes and imposes penalties for non-compliance. This study critically evaluates the RTS Act’s effects on Kerala’s administrative culture, addressing its achievements and the obstacles faced in its execution. While the RTS Act has promoted greater public involvement and accountability in service delivery, it has also revealed significant weaknesses within the administrative system. This article thoroughly analyses the Act’s effect on administrative reforms and assesses its wider significance for governance in the state.